That's my stapler: vulnerable narcissists and organizational territoriality. Issue 4 (8th January 2020) - Fennimore, Anne
Abstract : Purpose: This paper aims to examine two underexplored topics in organizations, i.e. vulnerable narcissists in organizational settings and possible effects of territorial infringements among vulnerable narcissistic employees. The movie, Office Space, illustrates prototypical employee behavior mixed with comedically maladaptive personalities in a modern organizational context. However, the arson committed by character, Milton Waddams, suggests that some employees, especially those with disordered personalities, might violently respond to perceived territorial infringements. Design/methodology/approach: This conceptual paper combines personality factors with territorial behavior to examine employee reactions to perceived injustices. Theoretical and practical implications are offered, as well as future research directions. Findings: The argument presented suggests that the vulnerable narcissists may initiate destructive behavior in organizations with ego threats like territorial infringements. While anger is a natural defensive reaction, vulnerable narcissists are more likely to behave aggressively toward perceived territorial infringements due to their general negative affect. Practical implications: Employees may react to infringement over seemingly subjective things; thus, managers must understand the nature of ownership by addressing territorial claims. Managers must remain cognizant that some disordered personalities are prone toward fulfilling threats, including organizational sabotage, deviance and white-collar crime. Environmental conditions can also compound the negative behavior of personalities like vulnerable narcissists in the workplace. Originality/value: This conceptual paper adds to the organizational behavior literature and contributes to the fields of psychology and territoriality by exploring vulnerable narcissists in organizational settings and by considering the magnitude of defensive behavior toward perceived infringements.